2006
DOI: 10.1590/s0100-204x2006000800011
|View full text |Cite
|
Sign up to set email alerts
|

Absorção e redução de nitrato em duas cultivares de arroz na presença de alumínio

Abstract: Resumo -O objetivo deste trabalho foi estudar os efeitos do alumínio (Al) sobre a absorção e a redução de nitrato, em duas cultivares de arroz: Fernandes (tolerante) e Maravilha (sensível), expostas a 0 e 500 µM de Al. Depois de 21 dias de crescimento, foram determinados o comprimento, a produção de matéria seca, os teores de Al e de nitrato e a atividade in vitro da redutase do nitrato (RN), nas raízes e na parte aérea, bem como as constantes cinéticas de absorção de nitrato pelas raízes. O Al reduziu o cresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
(28 reference statements)
2
9
0
5
Order By: Relevance
“…Al 3+ solubility increases under pH below 5.5 and its toxicity is particularly severe under pH below 5.0 (Fageria, 1998). Justino et al (2006) found that Al 3+ has a wide range of action on plant metabolism, this probably being the reason why its mechanism of action is not well known yet. However, it is known that the negative effect of aluminum does not affect calcium absorption directly but rather through root growth inhibition, decreasing Ca 2+ absorption, regardless of the direct effect of aluminum on the absorption process (Menosso et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Al 3+ solubility increases under pH below 5.5 and its toxicity is particularly severe under pH below 5.0 (Fageria, 1998). Justino et al (2006) found that Al 3+ has a wide range of action on plant metabolism, this probably being the reason why its mechanism of action is not well known yet. However, it is known that the negative effect of aluminum does not affect calcium absorption directly but rather through root growth inhibition, decreasing Ca 2+ absorption, regardless of the direct effect of aluminum on the absorption process (Menosso et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Justino et al (2006), when evaluating P uptake and tolerance of rice cultivars submitted to Al 3+ toxicity, observed a high variability between the cultivars tested regarding the uptake capacity of P. Thus, a hypothesis can be raised that, although Al 3+ decreases the accumulation of P in the roots of Maravilha cultivar ( Figure 2D), the plants have an efficient mechanism of translocation of P to shoot. In addition to the effect of P in the interior of the plant, the existence of relationship between the availability of P and Al 3+ in the soil solution is worth mentioning, in which, while increasing the concentration of Al 3+ , the concentration of P is decreased by the formation of precipitates between the ions in question (Sousa et al, 2007).…”
Section: Resultsmentioning
confidence: 97%
“…There was also a decrease in N accumulation in the shoot ( Figure 1C). Al 3+ reduces N uptake and nitrate reductase activity (Justino et al, 2006). Most of the N is uptake by plants in the form of nitrate and the enzyme nitrate reductase acts in the first phase of the reduction of nitric N to nitrite and then to ammonia, mediated by the enzyme nitrite reductase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses resultados podem estar relacionados à resposta diferenciada da enzima redutase do nitrato, que geralmente apresenta sensibilidade ao Al +3 , como já demonstrado por alguns autores (JUSTINO et al, 2006;CRUZ et al, 2011).…”
Section: Resultsunclassified